Conformal multi band antenna for personal mobility devices - Muhammad Zaki Subehi (Nanyang Technological University, 2021)
Over recent years, there has been a rapid rise in communications technology. Antennas and satellites have greater processing power, efficiency, and communication range [1]. These instruments can relay information and receive data at fast speeds; this allows communication devices, such as mobile phones and tablets to have a greater number of functionalities, for example, Global Positioning Systems (GPS), autonomous control and real-time traffic data information, which has brought improvement in our daily lives [2]. It has become common for motor vehicles such as cars and vans to have such devices installed into them. Despite this, there has been a lack of such communication devices being installed to Personal Mobility Devices (PMDs) such as e-scooters or motorized wheelchairs. As major cities around the world are getting more urbanised, there has been a greater demand for PMDs for commute. However, this has led to increased scrutiny in such devices as well due to safety concerns. Therefore, there is a great need to ensure that users of PMDs can still travel about without posing a risk to other commuters’ safety. Modifications can be made to the PMD to improve its user-friendliness and safety. In the experiments that will be conducted, a conformal multi band antenna will be designed via the of ANSYS HFSS (High Frequency Structure Simulator) for the purpose of PMD usage. Various variables of the antenna will be compared and simulated to obtain satisfactory results for the best possible antenna to be designed.